Impact of sectoral allocation of foreign aid on gender equity and human development - Lynda Pickbourn; Léonce Ndikumana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
While developing countries have made some progress in achieving human development since the turn of the century, many are still lagging behind in important human development goals such as education, health, nutrition and access to clean drinking water and improved sanitation. Moreover, gender equity remains a major challenge in most countries. In this paper, we examine the role that foreign aid plays in generating these outcomes, using panel data from OECD-DAC on the sectoral allocation of development aid, in conjunction with country-level data on public expenditures, human development outcomes and other economic, social and political indicators. Specifically, the paper attempts to assess whether the volume of aid and its sectoral allocation have an impact on human development outcomes and gender equity. We find that the impact of aid on many of the outcomes we study is largely dependent on initial levels of human development and per capita income. The results on the impact of aid vary by type of development outcome. While aid appears to be effective in reducing maternal mortality as well as the gender gap in youth literacy regardless of initial conditions, its effects are at best mixed for other indicators. The paper points to a number of policy issues that deserve further investigation.
Keywords: O1; O2; D0; E0; 330; foreign aid; human development; gender equity; education; health